2019
DOI: 10.1021/acs.langmuir.9b01955
|View full text |Cite
|
Sign up to set email alerts
|

Zn+–O Dual-Spin Surface State Formation by Modification of ZnO Nanoparticles with Diboron Compounds

Abstract: ZnO semiconductor oxides are versatile functional materials that used in photoelectronic, catalysis, sensing, etc. The Zn +-Osurface electronic states of semiconductor oxides were formed on ZnO's surface by Zn 4s, O 2p orbitals coupling with the diboron compound's B 2p orbitals. The formation of spin coupled surface states was based on the spin orbit interaction on the interface, which has not been reported before. It shows that the semiconductor oxide's spin surface states can be modulated by regulating surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In comparison with the unirradiated ZIF-8-T3, two new peaks appear at g ¼ 2.0038 and g ¼ 1.9600 in the EPR spectra of the irradiated one, which are ascribed to the absorbed cO 2 À and the paramagnetic Zn + centers, respectively. 46,47 Therefore, it can be induced that under sunlight irradiation, the electrons generated by ligand (via LMCT) or semiconductor (from VB to CB) would transfer to Zn 2+ to produce paramagnetic Zn + sites, as shown in eqn (1)-(3). Then, cO 2 À radicals are generated by electron transfer from Zn + to O 2 (eqn (4)).…”
Section: Mechanisms Of the Enhanced Photocatalytic Activity Of Zif-8-mentioning
confidence: 99%
“…In comparison with the unirradiated ZIF-8-T3, two new peaks appear at g ¼ 2.0038 and g ¼ 1.9600 in the EPR spectra of the irradiated one, which are ascribed to the absorbed cO 2 À and the paramagnetic Zn + centers, respectively. 46,47 Therefore, it can be induced that under sunlight irradiation, the electrons generated by ligand (via LMCT) or semiconductor (from VB to CB) would transfer to Zn 2+ to produce paramagnetic Zn + sites, as shown in eqn (1)-(3). Then, cO 2 À radicals are generated by electron transfer from Zn + to O 2 (eqn (4)).…”
Section: Mechanisms Of the Enhanced Photocatalytic Activity Of Zif-8-mentioning
confidence: 99%
“…[12] It has been reported that diboron compounds with BÀBb onds can serve as electron donors and contribute reductive sites to the surface of TiO 2 , ZnO,SnO 2 ,Nb 2 O 5 ,and In 2 O 3 via strong interfacial coupling, which affords 1000 times greater visible light response to enhance the performance of perovskite solar cells. [13] Therefore,r eductive boron may hold ag reat promise to serve as am etal-free element to facilitate Fe II regeneration in the Fenton reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Organic diboron species have been used to modified semiconductor oxide materials due to their unique Lewis acid character and reducing ability [16][17][18]. Facilitated by the Lewis acid-base interaction between B center of the diboron reagent and the surface bridging O 2c of semiconductor oxidematerials (e.g., TiO 2 , ZnO, SnO 2 ) nanoparticles, the adsorption of diboron species onto these nanoparticles results in spontaneous electron transfer, leading to various important transformations [16,17]. This strategy offers an effective approach for functionalizing the fiber structure of lubricating grease.…”
Section: Introductionmentioning
confidence: 99%